Penerapan pendidikan seksual dengan media visual storytelling pada anak usia dini ”Kujaga Diriku” - Rahmi, Dian; Rikayoni, Rikayoni (JOURNAL of Public Health Concerns, 2025)
Background: Cases of sexual violence against children in Indonesia remain a serious problem and are increasing every year. One preventative measure that can be implemented is through the implementation of early sexual education delivered in a developmentally appropriate manner. Sexual education is crucial for helping children gain self-awareness from an early age and protecting them from various sexual crimes. To implement sex education for children, teachers need new innovations to develop children's knowledge of sex. One way to do this is through the use of learning materials and media. Purpose: To provide knowledge about sexual education for early childhood using visual storytelling as a promotional and preventive measure against child sexual violence. Method: This Community Service activity was conducted on October 7, 2025, at Lillah Kindergarten in Padang City. The study subjects included three teachers, five parents, and 50 children from groups A and B (aged 4–6 years). The material was delivered through a video presentation of "I Take Care of Myself" and an animated story (visual storytelling) that the participants watched and followed along with the movements. This educational activity also included movement instructions with demonstrations. Data analysis used the Miles and Huberman model to assess respondents' knowledge descriptively. Results: The children demonstrated high enthusiasm and were able to understand the concept of "my body is mine" and how to reject inappropriate touch. 95% of the children accepted the differences between male and female body parts, 90% could correctly name private body parts, 97% were able to interpret good and bad touch, and 100% of the children were able to verbally reject them. Teachers played an active role as facilitators, while parental involvement reinforced learning at home. Conclusion: The visual storytelling-based early childhood sexuality education approach "Kujaga Diriku" (I Protect Myself) has proven effective in improving young children's understanding of self-protection. The illustrated story and animated video media help children understand moral messages in a concrete, enjoyable, and contextual way. Collaboration between teachers and parents is a crucial factor in the success of this program. Suggestion: It is hoped that the results of this study can form the basis for developing policies and child protection education modules based on local culture that are easy to implement in early childhood education institutions and contribute to strengthening the role of community nurses and educators in promotive and preventive efforts against child sexual violence. Keywords: Early childhood; Sexual education; Sexual violence prevention; Visual storytelling Pendahuluan: Kasus kekerasan seksual terhadap anak di Indonesia masih menjadi masalah serius dan meningkat setiap tahun. Salah satu upaya preventif yang dapat dilakukan melalui penerapan pendidikan seksual dini yang disampaikan dengan cara yang sesuai dengan perkembangan anak. Pendidikan seksual sangat penting untuk membantu anak memperoleh kesadaran diri sejak dini dan melindungi anak dari berbagai kejatahan seksual. Untuk melakukan proses pendidikan seks pada anak, maka guru memerlukan suatu inovasi baru dalam mengembangkan pengetahuan seks anak yang lebih baik. Salah satunya melalui penggunaan materi dan media pembelajaran. Tujuan: Untuk memberikan pengetahuan tentang pendidikan seksual pada anak usia dini dengan media visual storytelling sebagai upaya promotif-preventif terhadap kekerasan seksual anak. Metode: Pengabdian Kepada Masyarakat ini dilaksanakan pada tanggal 7 Oktober 2025 di TK Lillah Kota Padang. Subjek penelitian meliputi 3 orang guru, 5 orang wali murid dan 50 anak yang terdiri dari kelompok A dan B (usia 4–6 tahun). Menyampaikan materi dengan pemutaran video pembelajaran kujaga diriku dan cerita dalam bentuk animasi (visual storytelling) yang ditonton dan gerakan nya diikuti oleh responden. Kegiatan edukasi ini juga disertai petunjuk gerakan dengan peragaan Analisis data menggunakan model Miles dan Huberman untuk melihat penilaian pengetahuan responden secara deskriptif. Hasil: Sikap anak-anak menunjukkan antusiasme tinggi dan mampu memahami konsep “tubuhku milikku” serta cara menolak sentuhan tidak pantas. Sebanyak 95% anak  menerima perbedaan anggota tubuh laki-laki dan peremupuan, 90%dapat menyebutkan bagian tubuh pribadi dengan benar, 97% mampu memaknai  sentuhan baik dan tidak baik, dan 100% anak dapat menolak secara verbal. Guru berperan aktif sebagai fasilitator, sedangkan keterlibatan orang tua memperkuat pembelajaran di rumah. Simpulan: Pendekatan pendidikan seksual dini berbasis visual storytelling “Kujaga Diriku” terbukti efektif meningkatkan pemahaman anak usia dini mengenai perlindungan diri. Media cerita bergambar dan video animasi membantu anak memahami pesan moral secara konkret, menyenangkan, dan kontekstual. Kolaborasi antara guru dan orang tua menjadi faktor penting dalam keberhasilan program ini. Saran: Diharapkan, hasil penelitian ini dapat menjadi dasar pengembangan kebijakan dan modul pendidikan perlindungan anak berbasis budaya lokal yang mudah diimplementasikan di lembaga PAUD dan memberikan kontribusi terhadap penguatan peran tenaga keperawatan komunitas dan pendidik dalam upaya promotif-preventif terhadap kekerasan seksual anak.